Inclusive Learning Innovation for Deaf Students Using Sign Language Through Augmented Reality Technology - Zusfindhana, Inna Hamida; Kismawiyati, Renalatama; Andiwijaya, Soni; Arumristanti, Eliya Tahta; Silanto, Wargo (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2026)
This study aims to develop Augmented Reality (AR)-based learning media to enhance sign language learning skills for deaf students in the Special Education Study Program at Universitas PGRI Argopuro Jember. The research method employed is the ADDIE development model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The analysis phase revealed that the sign language learning process still relies on conventional methods without the support of innovative media, indicating the need for an interactive technology-based solution such as AR. The developed media is an AR application featuring 3D models of hand and finger movements adapted from the SIBI Dictionary, designed based on VISUALS principles to ensure ease of use, accuracy, and precision in learning. Validation results from media experts indicated a feasibility percentage of 89.37%, while material experts rated it at 86.66%, both categorized as highly feasible. The application was implemented with 11 deaf students, showing an average usage effectiveness of 94.54%, along with positive responses regarding ease of use, information accuracy, and flexibility in learning sign language anytime and anywhere. Evaluation was conducted using a Likert-scale questionnaire to measure the application's effectiveness. The findings demonstrate that AR-based learning media is highly effective in improving sign language comprehension and providing an inclusive learning experience for deaf students. This application is expected to serve as an innovative alternative learning medium in higher education to support technology-based inclusive education.